MENDESAIN KERANGKA TEMPAT TIDUR GANDA DENGAN MENGGUNAKAN KONSEP MATEMATIKA - M. Husna; L. Deswita; A. Sirait (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses how to design a double bed frame with standard-size material in the market using elementary mathematical concepts. Firstly, the double bed frame is designed, and then the frame is covered with plywood base material. To savea plywood base material and produce a stable bed frame, elementary mathematical concepts such as triangles congruent, Pythagoras theorem, quadratic equations, diﬀerential implicit, and the binomial theorem are used.